METHODOLOGY FOR USING ELECTRONIC LEARNING TOOLS IN THE EDUCATIONAL PROCESS ON THE SUBJECT PHYSICS - Abduvasiyev, Sardor (Физико-технологического образование, 2023)
When developing the content of physical education, the general principles of the unity of the content, structural and organizational aspects of teaching physics at different levels of general secondary education, as well as didactic principles, are taken into account. The paper shows that one of the professional tasks of a physics teacher is the task of using modern scientifically based methods, methods and means of teaching physics, including electronic teaching aids, information and computer technologies